2010
DOI: 10.1021/jp101939v
|View full text |Cite
|
Sign up to set email alerts
|

Modulated CO Oxidation Activity of M-Doped Ceria (M = Cu, Ti, Zr, and Tb): Role of the Pauling Electronegativity of M

Abstract: Many properties of dopants have been investigated to explore the key factor that influenced the CO oxidation activity of M-doped ceria (CeM). Nevertheless, these reports were controversial. Herein, the Pauling electronegativity (χP) of the M was presented as a convenient guide to screen a proper dopant for ceria. Kinetics results indicated that the T 10 (the temperature when CO conversion reached 10%) of CeM73 catalysts (Ce/M molar ratio was 7/3; M = Cu, Ti, Zr, and Tb) was linearly dependent on the χP of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 61 publications
0
70
0
Order By: Relevance
“…[9,18,33,34] Herein, CO oxidation reaction is chosen as a model reaction to assess the influence of the surface properties of the etched CeO 2 nanorods on their catalytic activity. [22,35,36] Obviously, the surface Ce 3+ fraction and the concentration of oxygen vacancies can significantly affect their catalytic activity, thus CO oxidation is a suitable model reaction to assess the changes of surface properties induced by redox chemical etching process on their catalytic activity. [22,35] The surface Ce 3+ sites play a crucial role in the absorption of CO molecules.…”
Section: Resultsmentioning
confidence: 99%
“…[9,18,33,34] Herein, CO oxidation reaction is chosen as a model reaction to assess the influence of the surface properties of the etched CeO 2 nanorods on their catalytic activity. [22,35,36] Obviously, the surface Ce 3+ fraction and the concentration of oxygen vacancies can significantly affect their catalytic activity, thus CO oxidation is a suitable model reaction to assess the changes of surface properties induced by redox chemical etching process on their catalytic activity. [22,35] The surface Ce 3+ sites play a crucial role in the absorption of CO molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Here the active sites are oxygen vacancies that expose the effective sites for CO adsorption and generate the active oxygen species. Therefore, the presence of oxygen vacancies is one of the critical parameters in determining the CO oxidation reaction [50]. In the present case, two types of dopants available that are isovalent (tetravalent) and aliovalent (trivalent).…”
Section: Catalytic Performancementioning
confidence: 96%
“…However, the CeO 2 is not a promising candidate for catalytic samples mainly due to its low catalytic activities [4][5][6][7][8][9]. Numerous reports have shown that the activity of ceria in total oxidation reactions is greatly enhanced by transitional metals like Co, Cu, Ti, Ni, and so on [10][11][12]. Co 3 O 4 is widely used as a non-noble metallic oxide in the catalysis field and shows very high CO oxidation activity in CO/O 2 mixtures even at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%